Klebsiella pneumoniae ST258 Negatively Regulates the Oxidative Burst in Human Neutrophils - Castillo, Luis A.; Birnberg-Weiss, Federico; Rodriguez-Rodrigues, Nahuel; Martire-Greco, Daiana; Bigi, Fabiana; Landoni, Veronica I.; Gomez, Sonia A.; Fernandez, Gabriela C. (Frontiers in Immunology, 2019)
The epidermic clone of K. pneumoniae (Kpn), sequence type 258 (ST258), carbapenamase producer (KPC), commonly infects hospitalized patients that are left with scarce therapeutic option since carbapenems are last resort antibiotics for life-threatening bacterial infections. To improve prevention and treatment, we should better understand the biology of Kpn KPC ST258 infections. Our hypothesis was that Kpn KPC ST258 evade the first line of defense of innate immunity, the polymorphonuclear neutrophil (PMN), by decreasing its functional response. Therefore, our aim was to evaluate how the ST258 Kpn clone affects PMN responses, focusing on the respiratory burst, compared to another opportunistic pathogen, Escherichia coli (Eco). We found that Kpn KPC ST258 was unable to trigger bactericidal responses as reactive oxygen species (ROS) generation and NETosis, compared to the high induction observed with Eco, but both bacterial strains were similarly phagocytosed and cause increases in cell size and CD11b expression. The absence of ROS induction was also observed with other Kpn ST258 strains negative for KPC. These results reflect certain selectivity in terms of the functions that are triggered in PMN by Kpn, which seems to evade specifically those responses critical for bacterial survival. In this sense, bactericidal mechanisms evasion was associated with a higher survival of Kpn KPC ST258 compared to Eco. To investigate the mechanisms and molecules involved in ROS inhibition, we used bacterial extracts (BE) and found that BE were able to inhibit ROS generation triggered by the well-known ROS inducer, fMLP. A sequence of experiments led us to elucidate that the polysaccharide part of LPS was responsible for this inhibition, whereas lipid A mediated the other responses that were not affected by bacteria, such as cell size increase and CD11b up-regulation. In conclusion, we unraveled a mechanism of immune evasion of Kpn KPC ST258, which may contribute to design more effective strategies for the treatment of these multi-resistant bacterial infections.